Model Strategi Pemasaran Jasa Konsultansi Kontraktor Di Kalimantan Selatan - Candra Yuliana; Retna Hapsari Kartadipura (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Most of the general public of service users have not understood the value of construction consultancy services. This inhibits market opportunities in the private sector for construction consulting services particularly in South Kalimantan. The objective of the research is to create an appropriate marketing strategy for corporation construction consultancy services in South Kalimantan.Strategies can be identified by SWOT analysis, AHP analysis and Importance Performance Analysis. This research is done by giving questionnaire to the service users and construction consulting firms in South Kalimantan. The result of the research are, a model of the marketing strategy of the construction consulting service, Strength-Opportunity strategy, grow and build strategy, service pricing strategy, and a basic strategy. This is a collaboration between the marketing-mix and service quality.